Ut transeant liberati. Ordo animae and Moral Transformation in Albert the Great’s Ethics (Doctor Virtualis, 2024)
This essay focuses on the theme of the order of the soul (ordo animae) in the ethics of Albert the Great (1200 ca.-1280). Drawing on several biblical sententiae and integrating them with the fundamental idea of Aristotle’s Nicomachean Ethics that the end of moral philosophy is to become good (ut boni fiamus), Albert conceives of ethics not as a mere “philosophical discourse”, to borrow a label from Pierre Hadot, but as an activity whose primary concern is the ordering – and the consequent transformation and liberation – of the self. The fact that Albert develops such a reflection in both his philosophical and biblical commentaries, relying in either case on both Aristotelian and scriptural sources, testifies then that his philosophy and biblical exegesis, which are usually portrayed as radically separate, are, in fact, deeply connected.
Keywords: Albert the Great; Christian Ethics; Aristotelian Ethics; Moral Transformation; Freedom